1999
DOI: 10.1017/s0305004198003387
|View full text |Cite
|
Sign up to set email alerts
|

On semiconjugation of entire functions

Abstract: Let f and h be transcendental entire functions and let g be a continuous and open map of the complex plane into itself with g∘f=h∘g. We show that if f satisfies a certain condition, which holds, in particular, if f has no wandering domains, then g−1(J(h))=J(f). Here J(·) denotes the Julia set of a function. We conclude that if f has no wandering domains, then h has no wandering domains. Further, we show that for given transcendental entire functions f and h, there are only countably many entire functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
160
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(164 citation statements)
references
References 13 publications
3
160
0
Order By: Relevance
“…(Note that the set B(f ) is independent of the choice of D. The set B(f ) was first introduced in [15] where we showed that it is equal to the set A(f ) introduced by Bergweiler and Hinkkanen in [6].) We show in [16] that if a transcendental entire function f satisfies the hypotheses of Lemma 2.1, then…”
Section: Introductionmentioning
confidence: 91%
“…(Note that the set B(f ) is independent of the choice of D. The set B(f ) was first introduced in [15] where we showed that it is equal to the set A(f ) introduced by Bergweiler and Hinkkanen in [6].) We show in [16] that if a transcendental entire function f satisfies the hypotheses of Lemma 2.1, then…”
Section: Introductionmentioning
confidence: 91%
“…(Such functions never belong to the Eremenko-Lyubich class B.) In fact, they showed that, for any transcendental entire function, the subset A(f ) ⊂ I(f ) of "points escaping at the fastest possible rate", as introduced by Bergweiler and Hinkkanen [BH99], has only unbounded components. Also, recently [Rem07] the weak form of Eremenko's conjecture was established for functions f ∈ B whose postsingular set is bounded (which applies, in particular, to the hyperbolic counterexample constructed in Theorem 1.1).…”
Section: Corollary (Meromorphic Functions With Logarithmic Singularitmentioning
confidence: 99%
“…Using arguments as in [6,36] one can show that the set A(f, D) does not depend on the choice of ρ, as long as ρ > ρ 0 . This justifies the notation where ρ is suppressed.…”
Section: Meromorphic Functions With a Direct Tractmentioning
confidence: 97%